Predicting Severe Disease and Critical Illness on Initial Diagnosis of COVID-19: Simple Triage Tools - Kurban, Lutfi Ali S.; AlDhaheri, Sharina; Elkkari, Abdulbaset; Khashkhusha, Ramzi; AlEissaee, Shaikha; AlZaabi, Amna; Ismail, Mohamed; Bakoush, Omran (Frontiers in Medicine, 2022)
Rationale This study was conducted to develop, validate and compare prediction models for severe disease and critical illness among symptomatic patients with confirmed COVID-19. Methods For development cohort, 433 symptomatic patients diagnosed with COVID-19 between April 15th 2020 and June 30th, 2020 presented to Tawam Public Hospital, Abu Dhabi, United Arab Emirates were included in this study. Our cohort included both severe and non-severe patients as all cases were admitted for purpose of isolation as per hospital policy. We examined 19 potential predictors of severe disease and critical illness that were recorded at the time of initial assessment. Univariate and multivariate logistic regression analyses were used to construct predictive models. Discrimination was assessed by the area under the receiver operating characteristic curve (AUC). Calibration and goodness of fit of the models were assessed. A cohort of 213 patients assessed at another public hospital in the country during the same period was used to validate the models. Results 186 patients were classified as severe while the remaining 247 were categorized as non-severe. For prediction of progression to severe disease, the three independent predictive factors were age, serum lactate dehydrogenase (LDH) and serum albumin (ALA model). For progression to critical illness, the four independent predictive factors were age, serum LDH, kidney function (eGFR) and serum albumin (ALKA model). The AUC for the ALA and ALKA models were 0.88 (95% CI, 0.86‒0.89) and 0.85 (95% CI, 0.83‒0.86) respectively. Calibration of the two models showed good fit and the validation cohort showed excellent discrimination, with an AUC of 0.91 (95% CI, 0.83‒0.99) for the ALA model and 0.89 (95% CI, 0.80‒0.99) for the ALKA model. A free web-based risk calculator was developed. Conclusions The ALA and ALKA predictive models were developed and validated based on simple, readily available clinical and laboratory tests assessed at presentation. These models may help frontline clinicians to triage patients for admission or discharge, as well as for early identification of patients at risk of developing critical illness.